2013
DOI: 10.4103/0019-5154.119953
|View full text |Cite
|
Sign up to set email alerts
|

Purely cutaneous rosai-dorfman disease with immunohistochemistry

Abstract: Background:The cutaneous form of Rosai-Dorfman disease (RDD) is a rare entity that manifests solely with skin papules or nodules and does not present with the usual myriad of symptoms of classical RDD.Aims:To analyze the most recent publications regarding cutaneous RDD to point out updated, relevant aspects regarding future directions for clinical recognition and management. To identify histopathologic and immunohistochemical findings in skin lesions that permit diagnosis.Materials and Methods:We present a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Treatment options for localized cutaneous LCH and RDD include surgical excision, cryotherapy, intralesional corticosteroid injection, radiotherapy, dapsone, acitretin, pulsed-dye laser, and close clinical monitoring. 8 , 12 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for localized cutaneous LCH and RDD include surgical excision, cryotherapy, intralesional corticosteroid injection, radiotherapy, dapsone, acitretin, pulsed-dye laser, and close clinical monitoring. 8 , 12 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…1 One study reported a predilection for the extremities. 2 Although very rare in children, CRDD including multifocal forms 3 has been described in pediatric patients. 4,5 Histopathology revealing histiocytic infiltration with emperipolesis is a useful non-pathognomonic clue for the diagnosis of RDD.…”
Section: Diagnosis: Cutaneous Rosai-dorfman Diseasementioning
confidence: 99%
“…Lorena Alexandra Mija MD 1 Nelson Piche MD 2 Viktor Kokta MD 3 Josee Dubois MD 4 Jerome Coulombe MD 5 1…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosai-Dorfman disease (RDD) which is also known as sinus histiocytosis with massive lymphadenopathy is an uncommon benign non-Langerhans cell histiocytic proliferative disorder of unknown aetiology 1 . It commonly affects lymph nodes with or without extra nodal involvement and massive painless cervical lymphadenopathy is the usual presentation.…”
Section: Introductionmentioning
confidence: 99%